TANTANGAN PENGEMBANGAN ILMU GIZI DALAM PENANGGULANGAN MASALAH GIZI (TEMU ILMIAH NASIONAL PERSAGI, 2023)
This paper aims to identify various challenges in the development and application of nutrition science in overcoming nutritional problems in Indonesia. The scope of discussion includes trends and projections of nutrition problems in Indonesia until 2030, changes and developments in the risk factor environment, changes in the paradigm of nutrition services. Identification of challenges associated with the implementation of the nutrition care process as a standard of professional care.In general, the problem of malnutrition, both stunting and wasting, is projected to decrease. Stunting is estimated to be below 20 percent (medium), meanwhile, wasting can be reduced below 5 percent as a public health problem. Micronutrient deficiency, especially nutritional anemia in pregnant women and children, is estimated to still be high, above 20 percent. While the prevalence of obesity will increase sharply, with an increase rate of 1 percent per year, and by 2030 is expected to reach above 30 percent. The increasing prevalence of obesity as a risk factor for NCDs among adults has an impact on the health care system and the economic burden of the disease. Demand for health nutrition care services has increased dramatically, awareness of the importance of disease prevention and health maintenance to improve quality of life is increasing.Developments in nutritional status and risk factors for nutritional problems show that there are still disparities and inequalities in nutrition services, both in terms of geography, demography and socio-economics. Innovation by the food and nutrition related industry that capitalizes on the growing consumer appetite for nutrition and health. Nutritional intake from the processed food group is increasing, and is estimated to reach around 50 percent of total energy. Accordingly, intake of sugar, salt and fat is projected to increase. On the other hand, a lifestyle characterized by a lack of movement, low consumption of fruits and vegetables causes an unbalanced diet.WHO (2020) has published Essential Nutrition Action, which is a list of recommended and not recommended nutritional interventions with various requirements. Implementation and choice of nutrition interventions are often faced with several problems. Some of the factors that are often faced are the selection of interventions themselves that do not consider existing studies. Nutrition interventions that should prioritize nutrition education and counseling are often neglected.There needs to be a transformation to improve nutrition by prioritizing on increasing the distribution of services (equity). In terms of nutrition services, it is encouraged that nutrition services should be an integral part of Universal Health Coverage. For this reason, it is necessary to strengthen nutritional human resources in professional services, improve the health system, transform financing, and data and information systems. In the field of food security, transformation is directed at overcoming inequalities in a healthier, more affordable food system in accordance with social culture.